FOREIGN INVESTORS AS SIGNPOSTS OF CHANGE? - Jensen, Camilla (Ekonomika, 2009)
The new market economies in Eastern Europe give a unique opportunity to study how agglomeration occurs due to the shift from a planner- constructed to a firm-driven economy. This paper it is investigated how foreign direct investment affects the existing economic geography. How are these changes taking place within the existing landscape of agglomerations inherited from socialism? Do foreign investors sustain existing patterns of agglomeration or are they signposts of change? A conditional logit model is implemented on a representative dataset combining the firm and regionallevel. Controls are made for region- and firm-specific factors such as market access, pre-existing industrial concentrations, regional policy and firm size. The results suggest that foreign investors are agents of both gradual and radical change in a new market economy such as Poland. With the exception of the capital region of Warsaw, past agglomerations are on the reverse and new ones are emerging; however, industrial inertia is quite strong outside Warsaw. Results also show that agglomeration economies in the make are significantly affected by cognitive distance. Foreign firms are more likely to go where other proximate peers (in terms of home country, industry and both) are going or have already gone.